Breathable moisture-regulating multi-layer composite silicon crystal decorative plate and preparation method thereof
Patent Information
- Application Number
- CN202611270503.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明的目的在于提供一种呼吸调湿型多层复合硅晶装饰板及其制备方法,以解决上述背景技术中提出现有调湿功能组分通常以物理填充方式分散于无机胶凝基体中,其与基体之间主要依靠机械嵌合作用结合,结合强度有限,在长期湿度循环过程中,调湿组分容易因水分反复吸附-释放引起界面微裂纹或局部脱落,导致有效调湿组分利用率降低,进而造成材料调湿性能稳定性不足的问题
[0033]本发明一种呼吸调湿型多层复合硅晶装饰板及其制备方法中,以天然沸石为调湿材料的基础骨架,通过正硅酸乙酯水解缩合在沸石表面形成多孔二氧化硅复合层,并进一步通过受控水解方式引入铝氧物种进行表面修饰,再利用二乙基磷酰乙基三乙氧基硅烷进行表面接枝改性,从而在调湿颗粒表面构建多级孔结构和具有极性的界面层,有利于提高材料对水蒸气的吸附与释放能力;同时,含磷硅烷改性层能够改善调湿颗粒与半水石膏、硅溶胶等无机胶凝组分之间的界面相互作用,从而降低调湿材料在反复湿度变化过程中发生界面脱粘和局部结构劣化的可能性,提高复合材料的调湿性能保持率;
Smart Images

Figure CN122880284A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building decoration materials technology, specifically to a breathable and moisture-regulating multilayer composite silicon crystal decorative panel and its preparation method. Background Technology
[0002] With the increasing demand for energy-efficient buildings, green building materials, and healthy indoor environments, inorganic composite decorative materials with functions such as regulating indoor humidity, improving the acoustic environment, and decoration have received widespread attention. Traditional decorative panels mainly include gypsum board, calcium silicate board, foam ceramic board, and silicon crystal decorative panels. Among them, gypsum-based materials have good fire resistance and a certain humidity regulation capability, while silicon-based porous materials have a high specific surface area and adsorption capacity. Lightweight inorganic materials such as expanded perlite and foam glass have advantages such as heat insulation, sound insulation, and reduced material density. Therefore, the composite construction of multifunctional decorative panels using various inorganic materials has become an important direction for the development of building interior materials. Currently, some silicon crystal decorative panels introduce porous materials such as natural zeolite, diatomaceous earth, and silica, utilizing their pore structure to achieve the adsorption and release of water vapor in the air, thereby achieving a certain humidity regulation effect. At the same time, by setting lightweight porous layers or perforated structures, the acoustic performance of the materials is improved to meet the requirements of the building environment for comfort and functionality.
[0003] However, existing humidity-regulating functional components are usually dispersed in inorganic cementitious matrices by physical filling. They are mainly bonded to the matrix by mechanical interlocking, which has limited bonding strength. During long-term humidity cycling, the humidity-regulating components are prone to interfacial microcracks or local detachment due to repeated adsorption and release of moisture, resulting in a decrease in the utilization rate of effective humidity-regulating components and thus insufficient stability of the material's humidity-regulating performance. In view of this, we propose a breathable humidity-regulating multilayer composite silicon crystal decorative panel and its preparation method. Summary of the Invention
[0004] The purpose of this invention is to provide a breathable, humidity-regulating multilayer composite silicon crystal decorative panel and its preparation method, in order to solve the problem mentioned in the background art that the existing humidity-regulating functional components are usually dispersed in an inorganic cementitious matrix by physical filling. The bonding between the components and the matrix mainly relies on mechanical interlocking, which has limited bonding strength. During long-term humidity cycling, the humidity-regulating components are prone to interfacial microcracks or local detachment due to repeated adsorption and release of moisture, resulting in a decrease in the utilization rate of effective humidity-regulating components and thus causing insufficient stability of the material's humidity-regulating performance.
[0005] To achieve the above objectives, the present invention provides a breathable humidity-regulating multilayer composite silicon crystal decorative panel, comprising a foamed gypsum covering layer, a silicon crystal humidity-regulating composite layer inside the foamed gypsum covering layer, and a perforated structure layer covered by the silicon crystal humidity-regulating composite layer.
[0006] The foamed gypsum coating layer is composed of hemihydrate gypsum, soybean protein foaming agent, nanocellulose, glass fiber, nanosilica, polycarboxylate superplasticizer and sodium citrate.
[0007] The silicon crystal humidity-regulating composite layer is composed of aluminosilicate silicon crystal humidity-regulating material, expanded vermiculite, alkaline silica sol, nano alumina, hemihydrate gypsum and sodium citrate;
[0008] The perforated structural layer is composed of pre-wetted expanded perlite, foam glass, silicate cement, lightweight ceramsite, and alkaline silica sol;
[0009] The aluminosilicate crystalline humidity-regulating material is obtained by using natural zeolite as the core, forming a porous silica composite layer on the surface, and further modifying the surface with aluminosilicate species and diethylphosphorylethyltriethoxysilane.
[0010] Preferably, the preparation method of the aluminum-silicon crystalline humidity-regulating material is as follows:
[0011] Add natural zeolite to deionized water at a mass ratio of 1:3-5, stir at 500-800 rpm for 30-40 min, and then treat with ultrasound at 200-400W for 15-20 min. Finally, centrifuge and dry to obtain pretreated zeolite.
[0012] Pretreated zeolite was dispersed in an ethanol-water-ammonia solution at a mass ratio of 1:10, wherein the volume ratio of ethanol, deionized water and 25% ammonia solution was 70:20:5. Tetraethyl orthosilicate was added, and the mixture was stirred at 400-600 rpm for 4-6 hours at 25-35℃. After washing and drying, zeolite@SiO2 composite powder was obtained.
[0013] Zeolite@SiO2 composite powder was dispersed in anhydrous ethanol solution of aluminum isopropoxide at a mass ratio of 1:5. After stirring evenly, deionized water was added to make the molar ratio of deionized water to aluminum isopropoxide 3-5:1. Hydrolysis was carried out at 25-40℃ for 1-2 hours, followed by aging for 2-4 hours. Then, solid-liquid separation was performed, and the powder was dried at 70-90℃ for 6-12 hours. Finally, it was heat-treated at 300-400℃ in air for 2-3 hours to obtain zeolite@aluminum-SiO2 composite powder.
[0014] Zeolite@aluminum-SiO2 composite powder was mixed with diethylphosphorylethyltriethoxysilane to obtain a mixture. The mixture was added to an ethanol / deionized water mixed solvent at a mass ratio of 1:8 (ethanol to deionized water mass ratio of 90:10). The pH of the system was adjusted to 4.0-5.0 with acetic acid. The reaction was carried out at 25-35℃ and 300-500rpm for 4-6 hours. After the reaction was completed, the mixture was vacuum dried at 60-80℃ for 6-12 hours to obtain an aluminum-silicon crystalline moisture-conditioning material.
[0015] Preferably, the mass ratio of the pretreated zeolite to tetraethyl orthosilicate is 1:0.15-0.40.
[0016] Preferably, the mass ratio of the zeolite@aluminum-SiO2 composite powder to diethylphosphorylethyltriethoxysilane is 100:0.5-4.5.
[0017] Preferably, the concentration of the aluminum isopropoxide anhydrous ethanol solution is 0.1-0.5 mol / L.
[0018] On the other hand, the present invention provides a method for preparing a breathable and humidity-regulating multilayer composite silicon crystal decorative panel, which includes the following steps:
[0019] S1.1, Prepare a perforated structure layer with through-hole structure;
[0020] S1.2. The moisture-conditioning composite slurry is coated on the outside of the perforated structure layer, so that the moisture-conditioning composite slurry fills the outer surface of the perforated structure layer and forms a silicon crystal moisture-conditioning composite layer.
[0021] S1.3 Place the perforated structure layer covered with the silicon crystal humidity-regulating composite layer inside the molding mold, and pour the foamed gypsum slurry into the molding mold so that the foamed gypsum slurry covers the outside of the silicon crystal humidity-regulating composite layer to form a foamed gypsum coating layer.
[0022] S1.4. Curing at 25-35℃ and relative humidity ≥90% for 24-48 hours to form an integral connection between the layers; demolding and surface finishing to obtain a breathable and humidity-regulating multi-layer composite silicon crystal decorative panel.
[0023] Preferably, in step S1.1, the method for preparing the perforated structure layer is as follows:
[0024] Mix 50-70 parts by weight of pre-wetted expanded perlite, 10-30 parts by weight of foamed glass and 5-15 parts by weight of lightweight ceramsite, and stir at 200-300 rpm for 10-20 minutes; add 10-20 parts by weight of silicate cement, 0.05-0.10 parts by weight of sodium citrate, 5-10 parts by weight of alkaline silica sol and 60-100 parts by weight of deionized water, and mix evenly to obtain a lightweight pore-forming slurry;
[0025] Lightweight pore-forming slurry is injected into a molding die with arrayed pins, allowing the arrayed pins to form through holes during the slurry curing process. The die is then left to stand at 25-35℃ and normal pressure for 30-60 minutes, pre-cured for 2-4 hours until the cement initially sets, and then the arrayed pins are removed. The die is then cured at normal pressure for 3-7 days to obtain a perforated structure layer with through holes of 3-8 mm in diameter and 5-15 mm in spacing.
[0026] Preferably, in step S1.2, the method for preparing the moisture-conditioning composite slurry is as follows:
[0027] Mix 40-60 parts by weight of aluminosilicate crystal moisture-conditioning material with 10-25 parts by weight of expanded vermiculite, and dry mix at 300-500 rpm for 15-20 min; add 10-20 parts by weight of alkaline silica sol with pH 8.5-9.5, and stir for 10-15 min; then add 10-20 parts by weight of hemihydrate gypsum, 1-5 parts by weight of nano alumina, 0.05-0.20 parts by weight of sodium citrate and 5-15 parts by weight of deionized water, and stir rapidly for 3-5 min to obtain the moisture-conditioning composite slurry.
[0028] Preferably, in step S1.3, the method for preparing the foamed gypsum slurry is as follows:
[0029] Add 0.3-1.5 parts by weight of soybean protein foaming agent to 50-100 times its weight of deionized water, and stir at 1000-2000 rpm for 5-10 minutes to form a foam liquid;
[0030] Mix 100 parts by weight of hemihydrate gypsum, 55-70 parts by weight of deionized water, 0.5-2.0 parts by weight of nanocellulose, 1-3 parts by weight of glass fiber, 1-5 parts by weight of nanosilica, 0.5-2.0 parts by weight of polycarboxylate superplasticizer and 0.05-0.20 parts by weight of sodium citrate, and stir at 300-500 rpm for 2-5 minutes; add foam liquid and stir at 100-200 rpm for 3-5 minutes to obtain foamed gypsum slurry.
[0031] Preferably, in S1.4, the thickness of the foamed gypsum coating layer is 3-10 mm; the thickness of the silicon crystal humidity-regulating composite layer is 10-30 mm; and the thickness of the perforated structure layer is 10-40 mm.
[0032] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0033] This invention discloses a breathable, humidity-regulating multilayer composite silicon crystal decorative panel and its preparation method. Natural zeolite is used as the basic framework of the humidity-regulating material. A porous silica composite layer is formed on the zeolite surface through the hydrolysis and condensation of tetraethyl orthosilicate. Further, aluminum oxide species are introduced for surface modification via controlled hydrolysis. Then, diethylphosphonyl ethyltriethoxysilane is used for surface grafting modification, thereby constructing a hierarchical porous structure and a polar interface layer on the surface of the humidity-regulating particles. This improves the material's ability to adsorb and release water vapor. Simultaneously, the phosphorus-containing silane-modified layer improves the interfacial interaction between the humidity-regulating particles and inorganic cementing components such as hemihydrate gypsum and silica sol, thereby reducing the possibility of interfacial debonding and local structural deterioration during repeated humidity changes and improving the humidity-regulating performance retention rate of the composite material.
[0034] In terms of structure, the present invention adopts a multi-layer composite structure consisting of a perforated structure layer, a silicon crystal humidity-regulating composite layer, and a foamed gypsum coating layer. The perforated structure forms a through-air channel, and the material density is reduced by using lightweight porous inorganic materials. At the same time, the outer foamed gypsum layer provides decoration, protection, and a certain overall structural support, thereby obtaining a multi-layer composite decorative board that combines humidity regulation, lightweight, and decorative and protective properties. Attached Figure Description
[0035] Figure 1 The humidity cycle humidity retention rate curves of the composite silicon crystal decorative panels in Example 1 and Comparative Examples 1-4 are shown.
[0036] Figure 2(a) shows the change rate of moisture absorption over time during the moisture absorption process of the composite silicon crystal decorative panels of Example 1 and Comparative Examples 1-4, and Figure 2(b) shows the change rate of moisture release over time during the moisture release process of the composite silicon crystal decorative panels of Example 1 and Comparative Examples 1-4. Detailed Implementation
[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0038] This invention provides a breathable and humidity-regulating multilayer composite silicon crystal decorative panel, comprising a foamed gypsum covering layer, a silicon crystal humidity-regulating composite layer inside the foamed gypsum covering layer, and a perforated structure layer covered by the silicon crystal humidity-regulating composite layer.
[0039] The foamed gypsum coating layer is composed of hemihydrate gypsum, soybean protein foaming agent, nanocellulose, glass fiber, nanosilica, polycarboxylate superplasticizer and sodium citrate.
[0040] The silicon crystal humidity-regulating composite layer is composed of aluminosilicate silicon crystal humidity-regulating material, expanded vermiculite, alkaline silica sol, nano alumina, hemihydrate gypsum and sodium citrate;
[0041] The perforated structural layer is composed of pre-wetted expanded perlite, foam glass, silicate cement, lightweight ceramsite, and alkaline silica sol;
[0042] The aluminosilicate crystalline humidity-regulating material is obtained by using natural zeolite as the core, forming a porous silica composite layer on the surface, and further modifying the surface with aluminosilicate species and diethylphosphorylethyltriethoxysilane.
[0043] The raw materials used in the embodiments of this invention are all commercially available industrial-grade products, with the following specific specifications: natural zeolite is clinoptilolite (Si / Al molar ratio 4.5-5.5, particle size 200-400 mesh); hemihydrate gypsum is α-type hemihydrate gypsum; diethylphosphorylethyltriethoxysilane (CAS No.: 757-44-8, purity ≥95%); tetraethyl orthosilicate (analytical grade, SiO2 content ≥28%); aluminum isopropoxide (purity ≥98%); alkaline silica sol (SiO2 content 30%, Na2O content ≤0.3wt%); nano-alumina (particle size 20-50nm, specific surface area ≥150m² / g). Nano-silica (specific surface area 200±50m² / g); polycarboxylate superplasticizer (water reduction rate ≥25%); nanocellulose (length 100-200nm, diameter 10-20nm); soybean protein foaming agent (hydrolyzed soybean protein, foaming ratio ≥20 times); expanded perlite (bulk density 80-120kg / m³, particle size 1-3mm); foamed glass (particle size 2-5mm, bulk density 150-200kg / m³); lightweight ceramsite (bulk density 300-500kg / m³, particle size 3-8mm); silicate cement is P·O42.5 ordinary silicate cement.
[0044] Example 1: A method for preparing a breathable and humidity-regulating multilayer composite silicon crystal decorative panel, comprising the following steps:
[0045] S1.1. Prepare a perforated structure layer with a thickness of 25 mm and a through-hole structure;
[0046] S1.2. The moisture-conditioning composite slurry is coated on the outside of the perforated structure layer, so that the moisture-conditioning composite slurry fills the outer surface of the perforated structure layer and forms a silicon crystal moisture-conditioning composite layer with a thickness of 20mm.
[0047] S1.3 Place the perforated structure layer covered with the silicon crystal humidity-regulating composite layer inside the molding mold, and pour the foamed gypsum slurry into the molding mold so that the foamed gypsum slurry covers the outside of the silicon crystal humidity-regulating composite layer, forming a foamed gypsum coating layer with a thickness of 7mm.
[0048] S1.4. Cure at 30℃ and relative humidity ≥90% for 48 hours to form an integral connection between the layers; demold and perform surface finishing to obtain a breathable and humidity-regulating multi-layer composite silicon crystal decorative panel.
[0049] The method for preparing the perforated structure layer is as follows:
[0050] Mix 60 parts by weight of pre-wetted expanded perlite, 20 parts by weight of foamed glass and 10 parts by weight of lightweight ceramsite, and stir at 300 rpm for 20 min; add 15 parts by weight of silicate cement, 0.10 parts by weight of sodium citrate, 8 parts by weight of alkaline silica sol and 80 parts by weight of deionized water, and mix evenly to obtain lightweight pore-forming slurry.
[0051] Lightweight pore-forming slurry is injected into a molding die with arrayed pins, allowing the arrayed pins to form through holes during the slurry curing process. The die is then left to stand at 30°C and normal pressure for 60 minutes, pre-cured for 3 hours until the cement initially sets, and then the arrayed pins are removed. The die is then cured at normal pressure for 7 days to obtain a perforated structure layer with through holes of 5 mm in diameter and 10 mm in spacing.
[0052] The preparation method of moisture-conditioning composite slurry is as follows:
[0053] Mix 50 parts by weight of aluminosilicate crystal moisture-conditioning material with 17 parts by weight of expanded vermiculite and dry mix at 400 rpm for 15 min; add 15 parts by weight of alkaline silica sol with pH 9.0 and stir for 15 min; then add 15 parts by weight of hemihydrate gypsum, 3 parts by weight of nano alumina, 0.1 parts by weight of sodium citrate and 10 parts by weight of deionized water, and stir rapidly for 5 min to obtain moisture-conditioning composite slurry.
[0054] The preparation method of foamed gypsum slurry is as follows:
[0055] Add 0.7 parts by weight of soybean protein foaming agent to 80 times its weight of deionized water and stir at 1500 rpm for 10 minutes to form a foam liquid; mix 100 parts by weight of hemihydrate gypsum, 62 parts by weight of deionized water, 1.2 parts by weight of nanocellulose, 2 parts by weight of glass fiber, 3 parts by weight of nanosilica, 1.2 parts by weight of polycarboxylate superplasticizer and 0.12 parts by weight of sodium citrate, and stir at 400 rpm for 5 minutes; add the foam liquid and stir at 200 rpm for 5 minutes to obtain foamed gypsum slurry.
[0056] The preparation method of aluminum-oxy-silicon crystalline humidity-regulating material is as follows:
[0057] Natural zeolite was added to deionized water at a mass ratio of 1:4. The mixture was stirred at 600 rpm for 35 min and then ultrasonically treated at 300 W for 20 min. The pretreated zeolite was obtained by centrifugation and drying.
[0058] Pretreated zeolite was dispersed in an ethanol-water-ammonia solution at a mass ratio of 1:10, wherein the volume ratio of ethanol, deionized water and 25% ammonia was 70:20:5. Tetraethyl orthosilicate was added, with a mass ratio of pretreated zeolite to tetraethyl orthosilicate of 1:0.28. The mixture was stirred at 500 rpm for 5 h at 30 °C, and then washed and dried to obtain zeolite@SiO2 composite powder.
[0059] Zeolite@SiO2 composite powder was dispersed in an anhydrous ethanol solution of aluminum isopropoxide at a mass ratio of 1:5 and stirred evenly. Then, deionized water was added to make the molar ratio of deionized water to aluminum isopropoxide 4:1. Hydrolysis was carried out at 30℃ for 2 hours and then aged for 3 hours. After solid-liquid separation, the powder was dried at 70℃ for 10 hours and then heat-treated at 300℃ for 3 hours in air atmosphere to obtain zeolite@aluminum-SiO2 composite powder.
[0060] Zeolite@aluminum-SiO2 composite powder was mixed with diethylphosphorylethyltriethoxysilane at a mass ratio of 100:2.5 to obtain a mixture. The mixture was then added to an ethanol / deionized water mixed solvent at a mass ratio of 1:8 (ethanol to deionized water mass ratio of 90:10). The pH of the system was adjusted to 4.5 using acetic acid. The reaction was carried out at 30℃ and 400 rpm for 5 h. After the reaction was completed, the mixture was vacuum dried at 60℃ for 12 h to obtain an aluminum-silicon crystalline moisture-conditioning material.
[0061] Example 2: The difference between this example and Example 1 is that the thickness of the silicon crystal humidity-regulating composite layer is 10mm.
[0062] Example 3: The difference between this example and Example 1 is that the thickness of the silicon crystal humidity-regulating composite layer is 30mm.
[0063] Example 4: The difference between this example and Example 1 is that 40 parts by weight of aluminosilicate moisture-regulating material are used.
[0064] Example 5: The difference between this example and Example 1 is that 60 parts by weight of aluminum oxide silicon crystal humidity-regulating material are used.
[0065] Example 6: The difference between this example and Example 1 is that the mass ratio of zeolite@aluminum-SiO2 composite powder to diethylphosphorylethyltriethoxysilane is 100:0.5.
[0066] Example 7: The difference between this example and Example 1 is that the mass ratio of zeolite@aluminum-SiO2 composite powder to diethylphosphorylethyltriethoxysilane is 100:4.5.
[0067] Determination of moisture absorption rate: Take the prepared and cured decorative board, cut no less than 3 representative samples from the middle of the board, with dimensions of 100mm × 100mm × complete thickness; place the samples in an oven at 23±2℃ to dry, weigh them once every 2 hours until the mass change rate of two consecutive weighings does not exceed 0.1%, and record the constant weight mass as m0; then place the samples in a constant temperature and humidity environment at 25±2℃ and relative humidity of 75±5%, keeping sufficient distance between the samples to ensure sufficient air circulation; to obtain the moisture absorption kinetic curve, after transferring to the constant temperature and humidity environment, weigh the sample mass at 0, 10, 20, 40, 60, 80, 100 and 120 minutes respectively, and calculate the moisture content change rate at the corresponding time according to the test time; then continue to place under the same conditions until 24 hours or when the mass change rate of two consecutive weighings does not exceed 0.1%, and record the final equilibrium mass m1; the moisture absorption rate is calculated according to the following formula: Moisture absorption rate = (m1-m0) / m0×100%.
[0068] Moisture release kinetics and moisture release rate determination procedure: First, following the moisture absorption rate test method described above, allow the sample to reach moisture absorption equilibrium at 25±2℃ and 75±5% relative humidity, and record the equilibrium mass m1; then, quickly transfer the sample to a constant temperature and humidity environment at 25±2℃ and 33±5% relative humidity, and weigh the sample at 0, 10, 20, 40, 60, 80, 100, and 120 min, recording the mass m at each time point. t And calculate the rate of change of moisture release at each time point according to the following formula: = (m1 - m t ) / m0×100%; The sample was placed under 33±5%RH conditions for 24 hours, and the mass m2 after 24 hours was recorded; The moisture release rate after 24 hours was calculated according to the following formula: Moisture release rate = (m1-m2) / m1×100%.
[0069] The procedure for determining the moisture retention rate after 20 humidity cycles is as follows: The initial moisture absorption rate A0 of the sample is tested according to the moisture absorption rate test method described above. Then, a humidity cycle is performed, with each cycle consisting of: maintaining the sample at 25±2℃ and 33±5% relative humidity for 24 hours, then adjusting to 75±5% relative humidity and maintaining for 24 hours, and then restoring to 33±5% relative humidity and maintaining for 24 hours, for a total of 72 hours; this process is repeated 20 times. After 20 cycles, the sample is placed back at 25±2℃ and 75±5% relative humidity for a moisture absorption test, yielding A0. 20 The humidity retention rate after 20 constant temperature and humidity cycles is calculated using the following formula: Humidity retention rate after 20 humidity cycles % = A 20 / A0×100%.
[0070] The procedure for determining the compressive strength of the composite layer is as follows: Cut at least five complete cross-sectional specimens from the middle of the cured decorative panel. The specimens should include the foamed gypsum coating layer, the silicon crystal moisture-regulating composite layer, and the perforated structural layer. The pressure surface of the specimen should be perpendicular to the thickness direction of the panel. Determine the specimen size based on the actual pressure area A of the specimen and ensure that the upper and lower pressure surfaces are parallel. Place the specimen between the upper and lower pressure plates of the universal testing machine, ensuring that the pressure surface is perpendicular to the loading axis and there is no obvious eccentricity. Continuously load the specimen at a stress increase rate of 0.5-1.0 MPa / s and record the maximum load F when the specimen fails. The compressive strength is calculated using the following formula: σc=F / A, where F is the maximum failure load in N; A is the pressure area in mm²; the final result is expressed in MPa.
[0071] Table 1 Performance data of multilayer composite silicon crystal decorative panels in Examples 1-7
[0072] Example 1 6.82 5.91 94.6 10.8 Example 2 5.74 4.86 91.8 10.1 Example 3 7.36 6.02 92.7 9.5 Example 4 5.48 4.73 90.9 11.6 Example 5 7.08 5.96 91.7 9.8 Example 6 6.05 5.02 87.9 10.5 Example 7 6.21 5.11 89.2 10.0
[0073] As shown in Table 1, with the increase in the thickness of the silicon crystal humidity-regulating composite layer from 10 mm to 20 mm, the moisture absorption rate, moisture release rate, and humidity retention rate after 20 humidity cycles all improved, as did the compressive strength. When the thickness of the humidity-regulating composite layer was further increased to 30 mm, the moisture absorption rate and moisture release rate continued to increase, but the humidity retention rate and compressive strength after 20 humidity cycles decreased. This is because appropriately increasing the thickness of the humidity-regulating composite layer can increase the effective content of the humidity-regulating material and the water vapor transport path, thereby improving the overall moisture absorption capacity. Meanwhile, when the thickness of the humidity-regulating layer increases from 10 mm to 20 mm... When the thickness reaches 30 mm, the load-bearing and stress transfer effects of the continuous cementitious phase in the composite structure are enhanced, which is beneficial to improving the overall compressive strength. When the humidity-regulating layer is further thickened to 30 mm, the relative proportion of the humidity-regulating material in the overall structure is further increased, while the relative load-bearing effect of the continuous cementitious phase decreases. The influence of internal pores, interface transition zones, and local defects on the overall stress increases, thus reducing the compressive strength. At the same time, a thicker humidity-regulating layer increases the mass transfer distance of water vapor in the composite structure, causing the response of the internal region to lag during humidity changes, thereby leading to a decrease in the cyclic humidity retention rate.
[0074] When the amount of aluminosilicate crystalline humidity-regulating material increased from 40 parts by weight to 50 parts by weight, the moisture absorption rate increased from 5.48% to 6.82%, the moisture release rate increased from 4.73% to 5.91%, and the humidity retention rate after 20 humidity cycles increased from 90.9% to 94.6%. This indicates that appropriately increasing the proportion of aluminosilicate crystalline humidity-regulating material can increase the utilization of effective moisture absorption sites and hierarchical pore structure, thereby improving water vapor adsorption and release capacity and cyclic humidity-regulating stability. When the amount added is further increased to 60 parts by weight, the moisture absorption rate... The moisture retention rate and moisture release rate reached 7.08% and 5.96% respectively, and continued to improve. However, the moisture retention rate after humidity cycling decreased to 91.7%, and the compressive strength decreased from 10.8 MPa in Example 1 to 9.8 MPa. This indicates that although excessive addition of moisture-regulating material can increase the content of moisture-absorbing active components, it will reduce the coating and connection effect between the particles of hemihydrate gypsum, alkaline silica sol and other cementitious materials, which will affect the continuous load-bearing structure inside the composite layer and reduce the effective interfacial bonding between the moisture-regulating material and the inorganic matrix.
[0075] When the amount of diethylphosphorylethyltriethoxysilane was increased from 0.5 parts by weight to 2.5 parts by weight, the moisture absorption rate, moisture release rate, and humidity retention rate after 20 humidity cycles all increased, indicating that an appropriate amount of phosphorus-containing silane can improve the functionalization of the composite particle surface and enhance the interfacial interaction between the particle surface and the inorganic cementing system through hydrolysis and condensation. When the amount of silane was further increased to 4.5 parts by weight, the moisture absorption rate, moisture release rate, and humidity retention rate after humidity cycles all decreased. Excessive silane underwent further condensation on the particle surface, causing the surface organic layer to thicken, which would shield some hydrophilic sites and pore entrances, restricting the transport of water molecules in the internal pore structure of the particles, thus reducing the overall humidity control performance.
[0076] Based on the above measurements, considering the comprehensive performance indicators such as moisture absorption rate, moisture release rate, humidity retention rate after humidity cycling, and compressive strength, Example 1 has a relatively balanced overall performance. Therefore, Example 1 is the optimal example.
[0077] Comparative Example 1: The difference between this comparative example and Example 1 is that diethylphosphorylethyltriethoxysilane was not added during the preparation of the aluminosilicate crystalline humidity-regulating material.
[0078] Comparative Example 2: The difference between this comparative example and Example 1 is that the aluminum oxide silicon crystal humidity-regulating material was not prepared by the steps of aluminum isopropoxide hydrolysis deposition, drying and heat treatment.
[0079] Comparative Example 3: The difference between this comparative example and Example 1 is that tetraethyl orthosilicate was not added during the preparation of the aluminosilicate silicon crystalline humidity-regulating material.
[0080] Comparative Example 4: The difference between this comparative example and Example 1 is that natural zeolite is used instead of aluminum oxide silicon crystal humidity control material.
[0081] Table 2 Performance data of multilayer composite silicon decorative panels of Examples 1 and Comparative Examples 1-4
[0082] Example 1 6.82 5.91 94.6 10.8 Comparative Example 1 5.96 5.08 84.7 9.9 Comparative Example 2 5.85 4.95 88.1 10.2 Comparative Example 3 5.72 4.86 82.6 10.0 Comparative Example 4 5.21 4.39 78.4 9.2
[0083] Compared to Example 1, Comparative Example 1, which did not use diethylphosphorylethyltriethoxysilane for surface modification, showed a decrease in moisture absorption, moisture release, and humidity retention rate after 20 humidity cycles, as well as a reduction in compressive strength. This is because diethylphosphorylethyltriethoxysilane hydrolyzes in a weakly acidic ethanol-water system to form silanol groups, which can condense with the hydroxyl groups on the surface of the zeolite@aluminum-SiO2 composite powder, thus facilitating the formation of Si-O-Si and / or Si-O-Al interfacial bonding structures. Simultaneously, the phosphorus-containing groups have strong polarity and can react with Ca in the inorganic cementing system. 2+ Furthermore, the surface hydroxyl groups generate coordination, hydrogen bonding, or ionic interactions, thereby improving the interfacial bonding stability between the humidity-regulating material particles and the inorganic cementitious matrix. Therefore, Comparative Example 1, which did not undergo silane surface modification, is more prone to interfacial microcracks or local bonding deterioration during repeated humidity changes, resulting in a decrease in humidity-regulating performance retention and mechanical properties.
[0084] Compared to Example 1, Comparative Example 2, which did not undergo aluminum isopropoxide hydrolysis deposition and subsequent heat treatment, showed a decrease in moisture absorption rate, moisture release rate, and humidity retention rate after 20 humidity cycles, as well as a reduction in compressive strength. This is because in Example 1, aluminum isopropoxide underwent controlled hydrolysis in an aqueous ethanol system, forming aluminum-containing hydroxyl / aluminum oxide precursors, which were deposited on the surface of the zeolite@SiO2 composite powder. After drying and heat treatment, an aluminum oxide species modification layer was formed on the surface of the composite particles. These surface aluminum oxide species can increase surface polar sites and form interfacial condensation structures with the hydroxyl groups on the silica surface, thereby improving the adsorption of water molecules and the interfacial compatibility between the humidity-regulating material and the inorganic cementitious phase. Without the aforementioned aluminum oxide species modification, the surface polar sites and interfacial bonding stability of the composite particles decreased, resulting in reduced moisture absorption and cycling stability.
[0085] Compared with Example 1, Comparative Example 3 did not contain tetraethyl orthosilicate, thus preventing the formation of a silica composite layer on the zeolite surface. Its moisture absorption rate, moisture release rate, and humidity retention rate after 20 humidity cycles all decreased, indicating that in the composite structure of this application, the silica composite layer helps increase the available pores and polar sites on the particle surface and improves the surface construction effect of subsequent alumina species and phosphorus-containing silanes. Simultaneously, as an intermediate interface layer, it helps improve the interfacial bonding between the humidity-regulating particles and the inorganic cementing system. Without the formation of the silica composite layer, the moisture adsorption-release capacity and cycling stability of the humidity-regulating material are affected.
[0086] Compared with Example 1, Comparative Example 4 directly used natural zeolite as the humidity-regulating material without silica coating, aluminum oxide species modification, or phosphorus-containing silane modification. Its moisture absorption rate and moisture release rate were reduced to 5.21% and 4.39%, respectively, and the humidity retention rate after 20 humidity cycles was only 78.4%, but the compressive strength still reached 9.2 MPa. The reason is that natural zeolite itself has a certain microporous structure and moisture absorption capacity, so it can still maintain a certain humidity-regulating performance. However, without surface and pore structure optimization, its water vapor transfer and interface stability are relatively limited. Under repeated humid heat, it is more likely to experience a decrease in pore utilization efficiency and a decrease in particle-matrix interface stability. Therefore, the humidity retention rate after cycling is significantly lower than that of Example 1.
[0087] Depend on Figure 1 It can be seen that as the number of humidity cycles increases, the humidity retention rate of each sample decreases, but the decrease in Example 1 is the smallest, and it still maintains 94.6% humidity retention performance after 20 cycles. This indicates that the multi-level humidity retention structure formed by SiO2 composite, aluminum oxide species modification and diethylphosphorylethyltriethoxysilane surface modification can improve the structural stability and water vapor adsorption-release performance retention of humidity retention materials under repeated humid and hot environments.
[0088] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A breathable and humidity-regulating multilayer composite silicon crystal decorative panel, characterized in that, It includes a foamed gypsum coating layer, a silicon crystal humidity-regulating composite layer inside the foamed gypsum coating layer, and a perforated structure layer covered by the silicon crystal humidity-regulating composite layer; The foamed gypsum coating layer is composed of hemihydrate gypsum, soybean protein foaming agent, nanocellulose, glass fiber, nanosilica, polycarboxylate superplasticizer and sodium citrate. The silicon crystal humidity-regulating composite layer is composed of aluminosilicate silicon crystal humidity-regulating material, expanded vermiculite, alkaline silica sol, nano alumina, hemihydrate gypsum and sodium citrate; The perforated structural layer is composed of pre-wetted expanded perlite, foam glass, silicate cement, lightweight ceramsite, and alkaline silica sol; The aluminosilicate crystalline humidity-regulating material is obtained by using natural zeolite as the core, forming a porous silica composite layer on the surface, and further modifying the surface with aluminosilicate species and diethylphosphorylethyltriethoxysilane.
2. The breathable and humidity-regulating multilayer composite silicon crystal decorative panel according to claim 1, characterized in that, The preparation method of the aluminum-silicon crystalline humidity-regulating material is as follows: Add natural zeolite to deionized water at a mass ratio of 1:3-5, stir at 500-800 rpm for 30-40 min, and then treat with ultrasound at 200-400W for 15-20 min. Finally, centrifuge and dry to obtain pretreated zeolite. Pretreated zeolite was dispersed in an ethanol-water-ammonia solution at a mass ratio of 1:10, wherein the volume ratio of ethanol, deionized water and 25% ammonia solution was 70:20:
5. Tetraethyl orthosilicate was added, and the mixture was stirred at 400-600 rpm for 4-6 hours at 25-35℃. After washing and drying, zeolite@SiO2 composite powder was obtained. Zeolite@SiO2 composite powder was dispersed in anhydrous ethanol solution of aluminum isopropoxide at a mass ratio of 1:
5. After stirring evenly, deionized water was added to make the molar ratio of deionized water to aluminum isopropoxide 3-5:
1. Hydrolysis was carried out at 25-40℃ for 1-2 hours, followed by aging for 2-4 hours. Then, solid-liquid separation was performed, and the powder was dried at 70-90℃ for 6-12 hours. Finally, it was heat-treated at 300-400℃ in air for 2-3 hours to obtain zeolite@aluminum-SiO2 composite powder. Zeolite@aluminum-SiO2 composite powder was mixed with diethylphosphorylethyltriethoxysilane to obtain a mixture. The mixture was added to an ethanol / deionized water mixed solvent at a mass ratio of 1:8 (ethanol to deionized water mass ratio of 90:10). The pH of the system was adjusted to 4.0-5.0 with acetic acid. The reaction was carried out at 25-35℃ and 300-500rpm for 4-6 hours. After the reaction was completed, the mixture was vacuum dried at 60-80℃ for 6-12 hours to obtain an aluminum-silicon crystalline moisture-conditioning material.
3. The breathable and humidity-regulating multilayer composite silicon crystal decorative panel according to claim 2, characterized in that, The mass ratio of the pretreated zeolite to tetraethyl orthosilicate is 1:0.15-0.
40.
4. The breathable and humidity-regulating multilayer composite silicon crystal decorative panel according to claim 2, characterized in that, The mass ratio of the zeolite@aluminum-SiO2 composite powder to diethylphosphorylethyltriethoxysilane is 100:0.5-4.
5.
5. The breathable and humidity-regulating multilayer composite silicon crystal decorative panel according to claim 2, characterized in that, The concentration of the aluminum isopropoxide anhydrous ethanol solution is 0.1-0.5 mol / L.
6. A method for preparing a breathable and humidity-regulating multilayer composite silicon crystal decorative panel, used to prepare the breathable and humidity-regulating multilayer composite silicon crystal decorative panel as described in any one of claims 1-5, characterized in that, The preparation method is as follows: S1.1, Prepare a perforated structure layer with through-hole structure; S1.
2. The moisture-conditioning composite slurry is coated on the outside of the perforated structure layer, so that the moisture-conditioning composite slurry fills the outer surface of the perforated structure layer and forms a silicon crystal moisture-conditioning composite layer. S1.3 Place the perforated structure layer covered with the silicon crystal humidity-regulating composite layer inside the molding mold, and pour the foamed gypsum slurry into the molding mold so that the foamed gypsum slurry covers the outside of the silicon crystal humidity-regulating composite layer to form a foamed gypsum coating layer. S1.
4. Curing at 25-35℃ and relative humidity ≥90% for 24-48 hours to form an integral connection between the layers; demolding and surface finishing to obtain a breathable and humidity-regulating multi-layer composite silicon crystal decorative panel.
7. The method for preparing the breathable and humidity-regulating multilayer composite silicon crystal decorative panel according to claim 6, characterized in that, In step S1.1, the method for preparing the perforated structure layer is as follows: Mix 50-70 parts by weight of pre-wetted expanded perlite, 10-30 parts by weight of foamed glass and 5-15 parts by weight of lightweight ceramsite, and stir at 200-300 rpm for 10-20 minutes; add 10-20 parts by weight of silicate cement, 0.05-0.10 parts by weight of sodium citrate, 5-10 parts by weight of alkaline silica sol and 60-100 parts by weight of deionized water, and mix evenly to obtain a lightweight pore-forming slurry; Lightweight pore-forming slurry is injected into a molding die with arrayed pins, allowing the arrayed pins to form through holes during the slurry curing process. The die is then left to stand at 25-35℃ and normal pressure for 30-60 minutes, pre-cured for 2-4 hours until the cement initially sets, and then the arrayed pins are removed. The die is then cured at normal pressure for 3-7 days to obtain a perforated structure layer with through holes of 3-8 mm in diameter and 5-15 mm in spacing.
8. The method for preparing the breathable and humidity-regulating multilayer composite silicon crystal decorative panel according to claim 6, characterized in that, In step S1.2, the preparation method of the moisture-conditioning composite slurry is as follows: Mix 40-60 parts by weight of aluminosilicate crystal moisture-regulating material with 10-25 parts by weight of expanded vermiculite, and dry mix at 300-500 rpm for 15-20 min; add 10-20 parts by weight of alkaline silica sol with pH 8.5-9.5, and stir for 10-15 min; then add 10-20 parts by weight of hemihydrate gypsum, 1-5 parts by weight of nano alumina, 0.05-0.20 parts by weight of sodium citrate and 5-15 parts by weight of deionized water, and stir rapidly for 3-5 min to obtain the moisture-regulating composite slurry.
9. The method for preparing the breathable and humidity-regulating multilayer composite silicon crystal decorative panel according to claim 6, characterized in that, In step S1.3, the preparation method of the foamed gypsum slurry is as follows: Add 0.3-1.5 parts by weight of soybean protein foaming agent to 50-100 times its weight of deionized water, and stir at 1000-2000 rpm for 5-10 minutes to form a foam liquid; Mix 100 parts by weight of hemihydrate gypsum, 55-70 parts by weight of deionized water, 0.5-2.0 parts by weight of nanocellulose, 1-3 parts by weight of glass fiber, 1-5 parts by weight of nanosilica, 0.5-2.0 parts by weight of polycarboxylate superplasticizer and 0.05-0.20 parts by weight of sodium citrate, and stir at 300-500 rpm for 2-5 minutes; add foam liquid and stir at 100-200 rpm for 3-5 minutes to obtain foamed gypsum slurry.
10. The method for preparing the breathable and humidity-regulating multilayer composite silicon crystal decorative panel according to claim 6, characterized in that, In S1.4, the thickness of the foamed gypsum coating layer is 3-10 mm; the thickness of the silicon crystal humidity-regulating composite layer is 10-30 mm; and the thickness of the perforated structure layer is 10-40 mm.